Pengaruh Current Ratio, Debt to Equity Ratio, dan Return On Assets Terhadap Return Saham Pada Perusahaan Transportasi yang Terdaftar di Bursa Efek Indonesia Selama Pandemi Covid-19 Periode 2019-2020 - Siregar, Lanina; Marliyah, Marliyah; Hasibuan, Nur Fadhilah Ahmad (Universitas Labuhanbatu, 2025)
This research aims to determine the partial and simultaneous influence of the variables Current Ratio, Debt to Equity Ratio, Return On Assets, and Return On Equity on Stock Returns. This type of research is quantitative research with secondary data in the form of financial reports of transportation companies listed on the Indonesia Stock Exchange (BEI) during the Covid-19 pandemic for the 2019-2020 period. The population of transportation companies on the IDX is 46 companies with samples taken using purposive sampling techniques. Based on the criteria, 24 companies were sampled in this research. So the total data for 2 years is 48 data. The data analysis used in the research is the classical assumption test, multiple linear regression analysis test, and hypothesis testing using SPSS version 26 software to process the data. The results of this research show that partially the current ratio has a significant value of 0,003 < 0,05, which means it has a significant effect on stock returns. The debt to equity ratio has a sigmificant value of 0,211 > 0,05, which means it has no significant effect on partial stock returns. Return on assets has a significant value of 0.046 <0.05, which means it has a significant effect on stock returns. Meanwhile, simultaneously the current ratio, debt to equity ratio, and return on assets have a significant influence on stock returns with a significant value of 0.026 < 0.05. Then the R Square test results show a value of 0.187 or the equivalent of 18.7%. From these results it can be explained that 18.7% of the independent variables CR, DER, and ROA are able to explain stock returns as the dependent variable. Meanwhile, the remainder, namely 81.3% of the possibility of stock returns, is explained by other variables not included in this research.